Implementasi Pembelajaran Akidah Akhlak Terhadap Kedisiplinan Peserta Didik MI/SD - Shinta Nuraini; Sri Haryanto; Vava Imam Agus Faisal (Student Research Journal, 2024)
The era of globalization easily brings about significant social changes and leads the current generation to experience an ethical and moral crisis. Therefore, the gonverment seeks to realize a cultured nation through strengthening the values of character education as stipulated in Presidential Regulation No. 87 of 2017. This reseacrh aims to: Understand the implementation of faith and morality learning towards dicipline among 5th-grade students at MI Al-Qur’an Al-Kayyis, and Determine the impacts of the implementation of faith and morality learning towards dicipline among 5th-grade students at MI Al-Qur’an Al-Kayyis. The method used in this reseacrh is qualitative method with a field reseacrh approach. The reseacrh findings indicate that the implementation of faith and morality learning towards the dicipline of 5th-grade students at MI Al-Qur’an Al-Kayyis is carried out through habituation, rules, and punishments. The habituation includes practicing the the 5S (smile, greet, welcome, politeness, and courtesy), habituation of prayers, memorization and recitation of surahs, habituation of performing Duha and Zuhur prayers in congregation, and extracurricular activities. These activities are an integration of faith and morality learning designed to shape individuals who are responsible for their own lives, possess strong dicipline, noble character, and are capable of facing life challenges wisely.